Relazioni pedagogiche Materiali di ricerca e formazione - OREFICE, CARLO (Strumenti per la didattica e la ricerca, 2013)
The volume starts from the monograph of the author entitled Per una pedagogia di "confine", deepening a series of pedagogical relationships, from the epistemological level of the relationship of pedagogy with other disciplines, to the theoretical level of learning "over the course of life", up to the methodological level the relationships researcher/educator, teacher/student, learner in an individual/cooperative situation. From this point of view, the author favours the anthropological-cultural contribution to the integration of educational interventions, making his own communicative and interactive methodologies for the qualification of learning and skills in training processes. The volume is a contribution for the basic pedagogical training of students enrolled in social-sanitary degree courses and other degrees that aim to shape educators.